2014
DOI: 10.1021/cn5000106
|View full text |Cite
|
Sign up to set email alerts
|

The Postnatal Development of d-Serine in the Retinas of Two Mouse Strains, Including a Mutant Mouse with a Deficiency in d-Amino Acid Oxidase and a Serine Racemase Knockout Mouse

Abstract: d-Serine, an N-methyl d-aspartate receptor coagonist, and its regulatory enzymes, d-amino acid oxidase (DAO; degradation) and serine racemase (SR; synthesis), have been implicated in crucial roles of the developing central nervous system, yet the functional position that they play in regulating the availability of d-serine throughout development of the mammalian retina is not well-known. Using capillary electrophoresis and a sensitive method of enantiomeric amino acid separation, we were able to determine tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 57 publications
1
14
0
Order By: Relevance
“…It has been shown that SR and D-serine expression normally changes dynamically in the retina with age, with D-serine being abundant earlier in development and declining in the first month of life. 76 In comparison to infant mice (3 weeks old), the adult mouse retina had limited Dserine and SR expression. 77 At present, it is not known why serine racemase and D-serine are so abundant early in development.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that SR and D-serine expression normally changes dynamically in the retina with age, with D-serine being abundant earlier in development and declining in the first month of life. 76 In comparison to infant mice (3 weeks old), the adult mouse retina had limited Dserine and SR expression. 77 At present, it is not known why serine racemase and D-serine are so abundant early in development.…”
Section: Discussionmentioning
confidence: 99%
“…LIF is the detection system which offers the best sensitivity of all the detectors used in CE and an evidence of this is the low LODs depicted in Table , generally in the nanomolar range even though the reported works did not employ additional preconcentration strategies . Moreover, in a recent published review article, it was demonstrated that LIF has been the most employed detector system in CE to determine chiral neuroactive molecules (e.g.…”
Section: Strategies To Enhance the Detection Sensitivitymentioning
confidence: 99%
“…Thus, derivatization agents must offer high stability, minimal hydrolysis products, low reaction times, and be compatible with the excitation source employed. In recent years, the most employed derivatization agents have been 7‐fluoro‐4‐nitro‐2,1,3‐benzoxadiazole (NBD‐F) , followed by naphthalene‐2,3‐dicarboxaldehyde , and FITC []. Moreover, carboxytetramethylrhodamine succinimidyl ester was employed as a novel reagent to derivatize amino acids, although LODs values were not reported.…”
Section: Strategies To Enhance the Detection Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…In mouse retina, levels of D‐Ser depend on its regulator enzymes (D‐amino acid oxidase, serine racemase), which are involved in the brain development. D‐Ser concentrations are quantified during the postnatal development in two different transgenic mice, one of which contained a loss‐of‐function point mutation for D‐amino acid oxidase while the other was a serine racemase knockout line . The total retinal D‐Ser is in a large amount at postnatal age and decreases as the mice matured into adulthood for wild and transgenic mice.…”
Section: Ce In Neurosciencesmentioning
confidence: 99%